High-Speed Optical-Beam Scanning by an Optical Phased Array Using Electro-Optic Polymer Waveguides - Yoshikuni Hirano; Yuji Miyamoto; Masato Miura; Yasushi Motoyama; Kenji Machida; Toshiki Yamada; Akira Otomo; Hiroshi Kikuchi (IEEE Photonics Journal)
Optical phased arrays (OPAs), which manipulate an optical beam by controlling the phase of light, are optical devices characterized by high speed, small size, light weight, and high reliability that make various applications possible. In this study, an eight-channel-waveguide OPA using an electro-optic (EO) polymer for phase control was fabricated. Very high-speed optical beam scanning with a frequency of 2 MHz was demonstrated by applying a driving waveform superimposing sinusoidal and rectangular-wave voltages. Furthermore, the EO polymer OPA can be operated with a low total-operation power consumption of 0.38 mW at a scanning speed of 500 kHz.